A 10-YEAR STUDY OF LENGTH OF STAY OF PSYCHIATRIC ADMISSIONS IN A TERTIARY CARE HOSPITAL IN RAWALPINDI - Yasir, Sadia; Jafri, Mahmood; Najeeb, Bahjat; Tamizuddin Nizami, Asad; Amir Malik, Muhammad Faisal; Afzal, Sara (Journal of Pakistan Psychiatric Society, 2024)
Objective To study the frequency of demographic variables along with the Length of Stay (LOS) in inpatient psychiatric facility related to category of psychiatric diagnosis. Design Retrospective chart review Place and Duration of Study The medical records of all admissions in Benazir Bhutto Hospital Rawalpindi spanning the period from January 2007 to December 2016 were reviewed. Patients and Methods Length of Stay (LOS) of patients admitted at the Institute of Psychiatry, Benazir Bhutto Hospital were noted. LOS greater than 10 days was considered as a cut-off point for lengthier stay. Results In this study involving 3,975 psychiatric inpatients, nearly 70% of the admissions were female, with depressive disorder being the most prevalent diagnosis. Over the decade, there was a notable reduction in the average length of hospital stay, decreasing from 13 to 9 days. A significant proportion (18.2%) of patients left against medical advice, with a higher percentage among females (19.3%) compared to males (15.5%). Patients were categorized into five age groups, and the highest admissions occurred among those aged 16 to 30 years (52.3%). The data also revealed fluctuations in the mean length of hospital stay over the years, ultimately averaging less than two weeks. Psychiatric diagnoses included a range of disorders, with depressive illness, schizophrenia, and bipolar affective disorder being the most common, while certain disorders like anorexia nervosa were less frequently encountered. Conclusion This study reveals that over the decade there is significant decrease in average hospital stays. This study underscores the need for further research to enhance psychiatric care in resource-limited regions.